The importance of molecular diagnostics and screening programs in monitoring and evaluation of colorectal cancer in the Republic of North Macedonia : Značaj molekularne dijagnostike i screening programa u praćenju i evaluaciji kolorektalnog karcinoma u Republici Sjevernoj Makedoniji - Trpkovska, Jovanka (Array, 2020)
Colorectal cancer (CRC) is one of the most common malignant diseases (12 % of the total) that occurs with an incidence of 15 – 30 new cases per 100,000 population per year in European Union countries. The risk of this disease during life depends on many factors such as age, diet, physical activity, personal and family predisposition. Several preventive measures can reduce the number of colorectal cancer patients. First of all, the regular screening which allows the detection of precancerous polyps or cancer in the early stage and their successful surgical removal. The purpose of this paper is to highlight the importance of screening programs as a preventive measure for the early detection of colorectal cancer and to reduce the morbidity and mortality of this disease. The strategy for improving the early detection of colorectal cancer also implies availability of useful information about the importance of screening programs for everyone as well as educating health care staff about the program itself. Number of newly registered colorectal cancer cases in 2009 in the Republic North Macedonia stands at 547 with a rate of 26.7 compared to 2018 with 839 newly registered cases with a rate of 40.4 which clearly indicates an increasing trend of colorectal cancer. Multidisciplinary approach to early detection of colorectal cancer, continuity of Program funding and quality of services will lead to reduction of morbidity and mortality of this type of cancer.